Reconstructing Implicit Meaning: Dalālat al-Muqtadā دَلَالَة المُقْتَضَى and the Challenge of Non-Cancellable Implicature in Arabic–English Translation (Al-Farooq Journal of Sciences, 2026)
This paper examines the concept of dalālat al-muqtadā (دَلَالَة المُقْتَضَى)  the implicature of what is required by the utterance  a key notion within the Arabic linguistic and jurisprudential tradition of uṣūl al-fiqh (أُصُول الفِقْه) (principles of Islamic jurisprudence), and investigates its relevance to contemporary translation studies between Arabic and English. Rooted in the classical taxonomies of meaning (dalālah, دَلَالَة) developed by Muslim scholars such as al-Ghazālī (الغَزَالِيّ, d. 505/1111), al-ʿAllāma al-Ḥillī (العَلَّامَة الحِلِّيّ, d. 726/1326), and al-Shāṭibī (الشَّاطِبِيّ, d. 790/1388), dalālat al-muqtadā refers to the meaning that is necessarily implied by a given linguistic expression, beyond its explicit semantic content. The paper argues that this classical concept shares significant theoretical terrain with Western pragmatic theories of implicature — particularly Grice's conversational implicature and Sperber and Wilson's Relevance Theory — while also possessing distinctive features shaped by the unique grammatical and rhetorical structures of Arabic.By conducting a comparative analysis of these frameworks and presenting case studies drawn from Qurʾānic (القُرْآن), legal, and literary texts, the paper demonstrates that translating dalālat al-muqtadā requires translators to navigate complex layers of implied meaning that conventional translation strategies often fail to capture. The study proposes an integrated analytical model that combines classical Arabic dalālah theory with contemporary pragmatic approaches, offering translation practitioners a more robust toolkit for handling implied meaning in Arabic–English translation.
Keywords: dalālat al-muqtadā (دَلَالَة المُقْتَضَى); Arabic linguistics; uṣūl al-fiqh (أُصُول الفِقْه); translation studies; implicature; pragmatics; Arabic–English translation; Relevance Theory